Effect of Ethyl Ester L-Lysine Triisocyanate addition to produce reactive PLA/PCL bio-polyester blends for biomedical applications. (April 2017) - Visco, Annamaria; Nocita, Davide; Giamporcaro, Alberto; Ronca, Sara; Forte, Giuseppe; Pistone, Alessandro; Espro, Claudia
Abstract: We report in this paper the effects of Ethyl Ester L-Lysine Triisocyanate (LTI) on the physical-mechanical properties of Poly(lactide)/Poly(ε-caprolactone) (PLA/PCL) polyesters blends. The PLA/PCL ratios considered were 20/80, 50/50 and 80/20 (wt/wt %) and LTI was added in amounts of 0.0–0.5-1.0 phr. PLA and PCL reacted with LTI during processing in a Brabender twin screw internal mixer to produce block copolymers in-situ. The resulting blends have been characterized by torque measurements, uniaxial tensile tests, Differential Scanning Calorimeter, contact angle measurements with a Phosphate Buffered Saline (PBS) solution, ATR analysis and morphological SEM observations. Experimental results highlighted how LTI enhanced interaction and dispersion of the two components, resulting into a synergic effect in mechanical properties. Mechanical and physical properties can be tailored by changing the blend composition. The most noticeable trend was an increase in ductility of the mixed polymers. Besides, LTI decreased blend's wet ability in PBS and lowered the starting of crystalline phase formation for both polymers, confirming an interaction among them. These reactive blends could find use as biomedical materials, e.g. absorbable suture threads or scaffolds for cellular growth. Graphical abstract: Highlights: The blends were based on PLA, PCL and L-Lysine Triisocyanate ( LTI). Reactive mixing reaction occurred during the materials processing. Mechanical torque, tensile test and physical analyses were performed in the blends. LTI compatibilizes PLA and PCL, improving the mechanical features of blends. Mechanical -physical properties can be tailored by changing the blend composition.